Theoretical knowledge of the nursing team in care for cardiorespiratory arrest in adults (Research, Society and Development, 2024)
Cardiovascular diseases represent a high death rate worldwide. Among the emergencies presented by cardiovascular complications, care for cardiorespiratory arrest must be studied by the nursing team in their practice. Because they act with greater representation, they can be the first to identify a PCR. This work aims to investigate the theoretical knowledge of nursing professionals at a Teaching Hospital regarding the care of Cardiorespiratory Arrest in adults. Carry out sociodemographic characterization and identify the knowledge of the nursing team about CPR in adults using the instrument “Cardiovascular resuscitation in adults on Basic Life Support with the use of an Automatic External Defibrillator in the Hospital Environment. This is a quantitative study, with a descriptive and exploratory design. The study was carried out online using the Google Forms platform, where two questionnaires entitled “sociodemographic characterization” and “Cardiopulmonary Resuscitation in adults on Basic Life Support with the use of an Automatic External Defibrillator in the hospital environment” were presented. nursing team professionals. In the research it was possible to identify in percentage the average number of correct answers related to each stage of the chain of survival which is composed of “Surveillance and prevention in Cardiorespiratory Arrest in Intra-Hospital Environment”. It is concluded that this study met the objective of identifying the socio-demographic characterization and the theoretical knowledge of the nursing team about CPR in adults and identified weaknesses in the theoretical knowledge regarding CPR of nursing professionals.